Multiplexed digital polymerase chain reaction as a powerful diagnostic tool - Gaňová, Martina; Zhang, Haoqing; Zhu, Hanliang; Korabečná, Marie; Neužil, Pavel (Biosensors & bioelectronics, 2021)
The digital polymerase chain reaction (dPCR) multiplexing method can simultaneously detect and quantify closely related deoxyribonucleic acid sequences in complex mixtures. The dPCR concept is continuously improved by the development of microfluidics and micro- and nanofabrication, and different complex techniques are introduced. In this review, we introduce dPCR techniques based on sample compartmentalization, droplet- and chip-based systems, and their combinations. We then discuss dPCR multiplexing methods in both laboratory research settings and advanced or routine clinical applications. We focus on their strengths and weaknesses with regard to the character of biological samples and to the required precision of such analysis, as well as showing recently published work based on those methods. Finally, we envisage possible future achievements in this field.
Keywords: Clinical applications; biosenzitivní techniky; Biosensing Techniques; Polymerase Chain Reaction; polymerázová řetězová reakce; Digital polymerase chain reaction; Duplex multiplexing; Higher order multiplexing; Multiplexing strategies; Absolute quantification